Design and Rationale of the National Tunisian Registry of Atrial Fibrillation: Protocol for a Prospective, Multicenter Trial - Ben Halima, Afef (JMIR Res Protoc, 2018)
BACKGROUND: Atrial fibrillation (AF) is an important health problem in Tunisia. A significant change in the epidemiological pattern of heart disease has been seen in the last 3 decades; however, no large prospective multicenter trial reflecting national data has been published so far. Robust data on the contemporary epidemiological profile and management of AF patients in Tunisia are limited. OBJECTIVE: The aim of this study is to analyze, follow, and evaluate patients with AF in a large multicenter nationwide trial. METHODS: A total of 1800 consecutive patients with AF by electrocardiogram, reflecting all populations of all geographical regions of Tunisia, will be included in the study, with the objective of describing the epidemiological pattern of AF. Patients will be officially enrolled in the National Tunisian Registry of Atrial Fibrillation (NATURE-AF) only if an electrocardiogram diagnosis (12-lead, 24-hour Holter, or other electrocardiographic documentation) confirming AF is made. The qualifying episode of AF should have occurred within the last year, and patients do not need to be in AF at the time of enrollment. Patients will be followed for 1 year. Incidence of stroke or transient ischemic attack, thromboembolic events, and cardiovascular death will be recorded as the primary end point, and hemorrhagic accidents, measurement of international normalized ratio, and time in therapeutic range will be recorded as secondary end points. RESULTS: Results will be available at the end of the study; the demographic profile and general risk profile of Tunisian AF patients, frequency of anticoagulation, frequency of effective treatment, and risks of thromboembolism and bleeding will be evaluated according to the current guidelines. Major adverse events will be determined. NATURE-AF will be the largest registry for North African AF patients. CONCLUSIONS: This study would add data and provide a valuable opportunity for real-world clinical epidemiology in North African AF patients with insights into the uptake of contemporary AF management in this developing region. TRIAL REGISTRATION: ClinicalTrials.gov NCT03085576; https://clinicaltrials.gov/ct2/show/NCT03085576 (Archived by WebCite at http://www.webcitation.org/6zN2DN2QX) REGISTERED REPORT IDENTIFIER: RR1-10.2196/8523